2016
DOI: 10.1007/s00394-016-1312-z
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of citrus flavanones by the probiotics Bifidobacterium longum and Lactobacillus rhamnosus

Abstract: These findings demonstrate the enzymatic potential of single strains of bifidobacterium and lactobacillus which may be involved in the colonic catabolism of OJ flavanones in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…The gastrointestinal tract plays a significant role in the metabolism and conjugation of polyphenols, because the polyphenols must pass through it before being absorbed into the bloodstream and distributed. However, not all polyphenols released in the distal GI tract are absorbed intact; many of them are metabolized by microbiota‐mediated breakdown, leading to low molecular weight phenolic catabolites . In some cases, these last ones are further metabolized locally and/or in other body districts (e.g., liver and kidney) before entering systemic circulation, and being then distributed and excreted .…”
Section: Absorption Uptake and Pharmacokineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gastrointestinal tract plays a significant role in the metabolism and conjugation of polyphenols, because the polyphenols must pass through it before being absorbed into the bloodstream and distributed. However, not all polyphenols released in the distal GI tract are absorbed intact; many of them are metabolized by microbiota‐mediated breakdown, leading to low molecular weight phenolic catabolites . In some cases, these last ones are further metabolized locally and/or in other body districts (e.g., liver and kidney) before entering systemic circulation, and being then distributed and excreted .…”
Section: Absorption Uptake and Pharmacokineticsmentioning
confidence: 99%
“…Some flavanone glycosides like hesperidin and naringin, both rutinosides, are not hydrolyzed in the small intestine but in the distal part of the same by α‐rhamnosidases originating from some resident bacteria. Recently, the catabolism of Citrus flavanones by the probiotics Bifidobacterium longum and Lactobacillus rhamnosus was investigated . The authors showed, as the two bacterial strains investigated possess enzymes, which may be involved in the catabolism of orange juice flavanones in vivo .…”
Section: Absorption Uptake and Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being strongly associated with citrus flavanone consumption, phenylhydracrylic acids do not seem to be produced during in vitro flavanone fermentations [15,157], suggesting that they are either purely endogenous metabolites, or at least a microbial catabolite which requires further metabolism after absorption. Volunteer studies have established that oral neohesperidin dihydrochalcone [92] and hesperetin [29] yield 3 -hydroxy-4 -methoxyphenylhydracrylic acid, i.e.…”
Section: Controls Used In Model Fermentations Have Clearly Demonstratmentioning
confidence: 99%
“…The phenol-explorer database is a useful compilation of good quality compositional data [3], but lacks data for the transformed anthocyanins, thearubigins and unextractable (poly)phenols [14]. Since phenolic acids are mostly monomeric phenols, flavonoids contain 2 phenolic rings, and polymerised flavonoids contain multiple phenolic rings, we designate the term "(poly)phenols" to cover this group [15].…”
mentioning
confidence: 99%